2019
DOI: 10.1097/j.pain.0000000000001745
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the putamen in pain and motor deficits in complex regional pain syndrome

Abstract: Complex regional pain syndrome (CRPS) develops after-limb injury, with persistent pain and deficits in movement frequently co-occurring. The striatum is critical for mediating multiple mechanisms that are often aberrant in CRPS, which includes sensory and pain processing, motor function, and goal-directed behaviors associated with movement. Yet, much remains unknown with regards to the morphological and functional properties of the striatum and its subregions in this disease. Thus, we investigated 20 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 90 publications
0
44
1
Order By: Relevance
“…In addition, one notable aspect revealed by this study is that the SMN subregions could be influenced by abnormal inputs from or outputs to the putamen, a component of the striatum. Literature has shown that the striatum affects the neuronal pathways underlying the inhibition effect of nociceptive stimulation [36]. These effects are mediated by the striatal dopamine D2 receptors which are associated with pain inhibitory circuitry of the caudal trigeminal nucleus [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one notable aspect revealed by this study is that the SMN subregions could be influenced by abnormal inputs from or outputs to the putamen, a component of the striatum. Literature has shown that the striatum affects the neuronal pathways underlying the inhibition effect of nociceptive stimulation [36]. These effects are mediated by the striatal dopamine D2 receptors which are associated with pain inhibitory circuitry of the caudal trigeminal nucleus [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one notable aspect revealed by this study is that the SMN subregions could be in uenced by abnormal inputs from or outputs to the putamen, a component of the striatum. Literature has shown that the striatum affects the neuronal pathways underlying the inhibition effect of nociceptive stimulation [36]. These effects are mediated by the striatal dopamine D2 receptors which are associated with pain inhibitory circuitry of the caudal trigeminal nucleus [37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent MRI-study showed a bilateral decrease in gray matter density in the putamen of CRPS patients. Additionally higher levels of pain and motor impairment were associated with an increased functional connectivity between the putamen and the pre−/postcentral gyri [4]. Based on these results there was evidence of a pathophysiological involvement of the basal ganglia for the development of clinical motor symptoms in CRPS.…”
Section: Case Reportmentioning
confidence: 71%